Effect of fluoride varnish with added casein phosphopeptide-amorphous calcium phosphate on the acid resistance of the primary enamel. Issue 1 (December 2016) - Tuloglu, Nuray; Bayrak, Sule; Tunc, Emine; Ozer, Fusun
Abstract Background This study aimed to investigate the effects of a fluoride varnish with added Casein Phosphopeptide-Amorphous Calcium Phosphate (CPP-ACP) treatments on acid resistance of primary teeth enamel. Methods Enamel specimens obtained from 40 primary incisors (for surface microhardness testing) and 40 primary molars (for demineralization depth measurement) were randomly divided into four groups (n  = 10 incisors and 10 molars) each according to surface treatment: no treatment (control), MI varnish (1–8 % sodium fluoride and 1–5 % CPP-ACP), Clinpro White (1–5 % sodium fluoride and <5 % modified tricalcium phosphate), Duraphat (<5 % sodium fluoride). Specimens were stored for 24 h in a moist environment. After varnish residues were removed, specimens were subjected to pH cycling. The effects of fluoride varnishes were evaluated according to surface microhardness, lesion depth and structural changes. Results were analyzed by ANOVA and Tukey's tests. Results The lowest changes in surface microhardness and lesion depth occurred in MI varnish group, followed by the Clinpro White, Duraphat and no treatment (control) group (for percentage of loss surface microhardness −20.80, −34.60, −57.80 and −73.40; for lesion depth values 23.60 μm ± 3.36, 29.85 μm ± 3.27, 40.37 μm ± 3.41 and 54.56 μm ± 4.16, respectively). Statistically significant differences in both surface microhardness and lesion depth were observed among all groups (P  < 0.05). Conclusions Within the limitations of this in vitro study, fluoride varnish containing CPP-ACP was more effective in increasing the acid resistance of primary enamel than other fluoride varnishes. However, further clinical research is needed to confirm these in vitro results.